Capacidades e performance dos Tribunais de Contas no Brasil - Puccioni, Felipe Galvão (2016)
This study aims at analyzing the relationship between the capacity, as defined by Brinkerhoff (2010), and the performance of Brazilian Courts of Accounts (Cortes de Contas). Capacity, in the current study, refers to the number of employees of each Court (Tribunal de Contas, TC), their budget, percentage of servants from their active staff and compliance with the constitutional rules in terms of their training. Performance was measured by the following variables: 'Productivity,' or the number of cases tried or considered by the Justices or Councilmembers; 'Initiative,' or number of 'in loco' audits carried out; 'Amount of fines and debts charged,' understood as the propensity to punish the Auditors Courts; and 'Level of rejection of government accounts,' which is defined as the reason for the number of previous opinions rejecting government accounts by the total number of opinions issued. The current study departs from that of Melo, Pereira and Figueiredo (2009), which identifies various relationships between the structure of the Court of Auditors/Public Finance Courts and its performance - offering new variables for a broader and more realistic analysis of the Auditors Courts' performance. The hypotheses of the study were tested through regression analysis using the minimum squares using statistical method. The data were collected directly from the Courts of Accounts. The tests confirmed that the number of staff in each Court positively influences all the performance variables referred to before, and that the larger the budget of each Court, the greater its productivity, its initiative and amount of fines and credits charged. This study also demonstrated that the larger the percentage of servants in the working staff of the Auditors Court, the greater its productivity, corroborating the theories of Evans (2004). Based on the data collected, we were able to verify that the average percentage of working servants in the Auditors' Court is 69%, whereas in the Judicial Courts the percentage is 89%. This shows that there is plenty of room for increasing the productivity of the auditing bodies. The resulting conclusion is that the greater the financial resources and personnel are, and the greater the percentage of civil servants is, the more productive, proactive and sanctioning the Court of Audits/Public Finance Courts are.